Hepatic artery and portal vein Doppler ultrasound reference values in children aged 0–17 years old. (May 2023) - Verhagen, Martijn V; Kwee, Thomas C; de Haas, Robbert J
Introduction: Doppler ultrasound of the portal vein peak systolic velocity and hepatic artery peak systolic velocity and resistive index in children is often performed during abdominal ultrasound for the assessment of liver and other abdominal pathology. However, evidence-based reference values are not available. We aimed to determine these reference values and to investigate whether they are age-dependent. Methods: Children who underwent abdominal ultrasound between 2020 and 2021 were retrospectively identified. Patients without hepatic or cardiac abnormalities at the time of ultrasound or during at least 3 months follow-up were eligible for the study. Ultrasound without hepatic hilum portal vein peak systolic velocity and/or hepatic artery peak systolic velocity and resistive index measurements were excluded. Age-dependent changes were analyzed using linear regression. Normal range reference values were described using percentiles for all ages, and for age subgroups. Results: One-hundred ultrasound examinations performed in 100 healthy children aged 0–17.9 years (median 7.8 years, interquartile range 1.1–14.1 years) were included. Ninety-nine portal vein peak systolic velocity and 80 hepatic artery peak systolic velocity and resistive index measurements were obtained. There was no significant association between portal vein peak systolic velocity and age (β = −0.056, p  = 0.68). There were significant associations between age and hepatic artery peak systolic velocity, and between age and hepatic artery resistive index (β = −0.873, p  = 0.04 and β = −0.004, p  < 0.001, respectively). Detailed reference values were provided for all ages, and for age subgroups. Conclusion: Reference values for the hepatic hilum portal vein peak systolic velocity, hepatic artery peak systolic velocity, and hepatic artery resistive index in children were established. Portal vein peak systolic velocity is not age-dependent, whereas hepatic artery peak systolic velocity and hepatic artery resistive index decrease when children get older.